The Effect of Transfer Pricing, Profitability and Political Connections on Tax Aggressiveness with Gender Diversity as a Moderating Variable - Nurjayanti, Nanik; Utami, Wiwik (Journal of Accounting and Finance Management, 2025)
This study aims to explore the impact of transfer pricing, profitability, and political connections on the level of tax aggressiveness, considering gender diversity as a moderating factor. The research sample consists of mining companies listed on the Indonesia Stock Exchange (IDX) during the period 2017 to 2022. The sample was selected using a purposive sampling method, resulting in 142 mining companies. The data used in this study are secondary, obtained from audited financial reports available at www.idx.co.id. Data analysis was performed using the MRA technique using IBM SPSS 22 statistical software. Transfer pricing is proxied by (TP), Profitability is proxied by (ROA), political connections are proxied by (dummy), tax aggressiveness is proxied by (ETR), gender diversity is proxied with (GD). Transfer pricing does not significantly affect tax aggressiveness, whereas profitability has a significantly positive affect, political connections do not significantly influence tax aggressiveness, gender diversity does not moderate the effect of transfer pricing on tax aggressiveness, but it strenghnes the relationship between profitability and tax aggressiveness, and weakens the effect of political connections on tax aggressiveness.